Effects of Telerehabilitation-Based Structured Home Program on Activity, Participation and Goal Achievement in Preschool Children with Cerebral Palsy: A Triple-Blinded Randomized Controlled Trial - Sinem Asena Sel; Mintaze Kerem Günel; Sabri Erdem; Merve Tunçdemir (MDPI AG, 2023)
A home program is implemented as an evidence-based mode of delivering services for physiotherapy and rehabilitation. Telerehabilitation is a method applied in physiotherapy modalities for children. This study aims to determine the effectiveness of usual care plus a Telerehabilitation-Based Structured Home Program on preschool children with cerebral palsy (CP) compared to usual care. Forty-three children aged 3-6 years (mean age 4.66 ± 1.08 years) with CP were randomly assigned to the Telerehabilitation-Based Structured Home Program and usual care groups. Their motor function was assessed with the Gross Motor Function Measure (GMFM); performance and satisfaction were evaluated with the Canadian Occupational Performance Measure (COPM); goal achievement was assessed with the Goal Attainment Scale (GAS); and activity and participation were evaluated with Pediatric Evaluation of Disability Inventory (PEDI). Participants were evaluated at baseline, immediately post-intervention (12 weeks) and at follow-up (24 weeks). There was a statistically significant difference between pre- and post-test GMFM, COPM, GAS and PEDI scores in the intervention and control groups (p < 0.001). The Telerehabilitation-Based Structured Home Program showed statistically significant changes in activity, participation and goal achievement after 12 weeks of intervention (p < 0.001). However, significant results were not obtained in the usual care group. The Telerehabilitation-Based Structured Home Program may be an effective method for preschool children with CP. (Registration number: NCT04807790; no = KA-20124/26.01.2021).